Renal effects of three endoaortic occlusion strategies in a swine model of hemorrhagic shock. Issue 11 (November 2019) - Hoareau, Guillaume L.; Tibbits, Emily M.; Simon, Meryl A.; Davidson, Anders J.; DeSoucy, Erik S.; Faulconer, E. Robert; Grayson, J. Kevin; Stewart, Ian J.; Neff, Lucas P.; Williams, Timothy K.; Johnson, M. Austin
Highlights: Renal blood flow alterations following resuscitative endovascular balloon occlusion of the aorta (REBOA) are complex. Following 45 min of supraceliac REBOA, renal blood flow returns to baseline values after 45 min. Infrarenal occlusion alone or following supraceliac occlusion did not provide reduce renal damage. Abstract: Introduction: Trauma patients are predisposed to kidney injury. We hypothesized that in shock, zone 3 REBOA would increase renal blood flow (RBF) compared to control and that a period of zone 3 occlusion following zone 1 occlusion would improve renal function compared to zone 1 occlusion alone. Materials and methods: Twenty-four anesthetized swine underwent hemorrhagic shock, 45 min of zone 1 REBOA (Z1, supraceliac), zone 3 REBOA (Z3, infrarenal), or no intervention (control) followed by resuscitation with shed blood and 5 h of critical care. In a fourth group (Z1Z3), animals underwent 55 min of zone 3 REBOA following zone 1 occlusion. Physiologic parameters were recorded, blood and urine were collected at specified intervals. Results: During critical care, there were no differences in RBF between the Z1 and Z3 groups. The average RBF during critical care in Z1Z3 was significantly lower than in Z3 alone (98.2 ± 23.9 and 191.9 ± 23.7 mL/min; p = 0.046) and not different than Z1. There was no difference in urinary neutrophil gelatinase-associated lipocalin-to-urinary creatinine ratio between Z1 and Z1Z3. Animals in the Z1Z3 group had a significant increase in the ratio at the end of the experiment compared to baseline [median (IQR)] [9.2 (8.2–13.2) versus 264.5 (73.6–1174.6)]. Following Z1 balloon deflation, RBF required 45 min to return to baseline. Conclusion: Neither zone 3 REBOA alone nor zone 3 REBOA following zone 1 REBOA improved renal blood flow or function. Following zone 1 occlusion, RBF is restored to baseline levels after approximately 45 min.